Online trapping and enrichment ultra performance liquid chromatography–tandem mass spectrometry method for sensitive measurement of “arginine-asymmetric dimethylarginine cycle” biomarkers in human exhaled breath condensate - Di Gangi, Iole Maria; Pirillo, Paola; Carraro, Silvia; Gucciardi, Antonina; Naturale, Mauro; Baraldi, Eugenio; Giordano, Giuseppe (Analytica chimica acta, 2012)
[Display omitted] ► Simultaneous quantification of “arginine-ADMA cycle” metabolites developed in EBC. ► EBC is a non-invasive matrix highly useful in patients with respiratory diseases. ► Method, fast, precise and accurate, is suitable in the pediatric clinical studies. ► Sensitivity is increased using on-line trapping and enrichment-UPLC–MS/MS method. ► EBC measurements in asthmatic adolescents confirm that ADMA is increased in asthma. Exhaled breath condensate (EBC) is a biofluid collected non invasively that, enabling the measurement of several biomarkers, has proven useful in the study of airway inflammatory diseases, including asthma, COPD and cystic fibrosis. To the best of our knowledge, there is no previous report of any analytical method to detect ADMA in EBC. Aim of this work was to develop an online sample trapping and enrichment system, coupled with an UPLC–MS/MS method, for simultaneous quantification of seven metabolites related to “Arginine-ADMA cycle”, using the isotopic dilution. Butylated EBC samples were trapped in an online cartridge, washed before and after each injection with cleanup solution to remove matrix components and switched inline into the high pressure analytical column. Multiple reaction monitoring in positive mode was used for analyte quantification by tandem mass spectrometry. Validation studies were performed in EBC to examine accuracy, precision and robustness of the method. For each compound, the calibration curves showed a coefficient of correlation (r2) greater than 0.992. Accuracy (%Bias) was <3% except for NMMA and H-Arg (<20%), intra- and inter-assay precision (expressed as CV%) were within ±20% and recovery ranged from 97.1 to 102.8% for all analytes. Inter-day variability analysis on 20 EBC of adult subjects did not demonstrate any significant variation of quantitative data for each metabolite. ADMA and SDMA mean concentrations (μmolL−1), measured in EBC samples of asthmatic adolescents are significantly increased (p<0.0001) than in normal controls (0.0040±0.0021 vs. 0.0012±0.0005 and 0.0020±0.0015 vs. 0.0002±0.0001, respectively), as well the ADMA/Tyr (0.34±0.09 vs. 0.12±0.02, p<0.0001) and the SDMA/Tyr ratio (0.10±0.04 vs. 0.015±0.004, p<0.0001). The proposed method features simple specimen preparation, maintenance of an excellent peak shape of all metabolites and reduced matrix effects as well mass spectrometer noise. Moreover, the possibility to perform different cycles of enrichment, using large injection volumes, compensated for the low concentration of analytes contained in EBC, leading to a good analytical sensitivity. Preliminary data obtained from asthmatic and healthy adolescents, demonstrated that the analytical method applied to EBC seems suitable not only for research purposes, but also for clinical routinely analysis.